Preliminary Design: Development of Capillarity e-Module Based Ethnoscience to Promoting Students’ Science Literacy - Mahbubah, Khoiro; Santoso, Agus; Djatmiko, Rahmad (Department of Physics Education, Universitas Mataram, 2025)
Promoting character and affecting local culture can also be through ethnoscience approach. This study aims to develop a Capillarity e-module based ethnoscience and determine the effectiveness of the module to increase students' scientific literacy. The method of this study is Research and Development, it utilized 3D+1I model (Define, Design, Develop and Implementation) that used to produce certain products and test the effectiveness of these products. Subject of this research 15 pre-service Science Education teachers at Universitas Islam Lamongan who were studying Fluids and Thermodynamics courses. The results showed that the development of Capillarity e-module based ethnoscience with an average percentage of validation on the feasibility aspect of the content, language feasibility, and feasibility of presenting correspondingly for 95.3%, 86.1% and 82.3% and a very feasible criteria. The effect of the implementation of Capillarity e-module based ethnoscience can promote pre-service science education teachers’ science literacy classical amounted to 93.75% Based on the results of this research concluded that the Capillarity e-module based ethnoscience effectively to increase pre-service science education teachers’ science literacy.